2018
DOI: 10.1186/s13195-017-0335-x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic proteins in CSF as potential novel biomarkers for prognosis in prodromal Alzheimer’s disease

Abstract: Background: We investigated whether a panel of 12 potential novel biomarkers consisting of proteins involved in synapse functioning and immunity would be able to distinguish patients with Alzheimer's disease (AD) and patients with mild cognitive impairment (MCI) from control subjects. Methods: We included 40 control subjects, 40 subjects with MCI, and 40 subjects with AD from the Amsterdam Dementia Cohort who were matched for age and sex (age 65 ± 5 years, 19 [48%] women). The mean follow-up of patients with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
96
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 50 publications
13
96
2
Order By: Relevance
“…Overall, despite the variable characteristics of these four modules, these results aligned well with the decreased abundance of neuronal-linked modules we have previously observed in the AD brain [10]. Furthermore, these findings support the large body of evidence implicating synaptic dysfunction and cellular hypometabolism in AD pathogenesis [34][35][36], as well as provide a global perspective on their underlying protein alterations in brain. In summary, systems-level analysis of our Brain1 proteome generated modules of protein co-expression with disease-specific alterations in AD consistent with many of our prior findings.…”
Section: Systems-based Analysis Of the Brain Proteome Reveals Modulessupporting
confidence: 87%
“…Overall, despite the variable characteristics of these four modules, these results aligned well with the decreased abundance of neuronal-linked modules we have previously observed in the AD brain [10]. Furthermore, these findings support the large body of evidence implicating synaptic dysfunction and cellular hypometabolism in AD pathogenesis [34][35][36], as well as provide a global perspective on their underlying protein alterations in brain. In summary, systems-level analysis of our Brain1 proteome generated modules of protein co-expression with disease-specific alterations in AD consistent with many of our prior findings.…”
Section: Systems-based Analysis Of the Brain Proteome Reveals Modulessupporting
confidence: 87%
“…Some of the proteins that we observe are reduced in AD synapses have been observed as CSF biomarkers associating with disease. For example, we observe a 25% decrease in neurexin 2 and over 30% decrease in neurogranin abundance in AD APOE 4 superior temporal gyrus compared to controls, whereas recently published biomarker studies observed increases in neurexin 2 and neurogranin in CSF of people with mild cognitive impairment or AD 36, 37, 38 . In another study of CSF, a group of 9 synaptic proteins (GluR2, GluR4, Neuroligin-2, Neurexin-3A, Neurexin-2A, Calsynytenin-1, Syntaxin-1B, Thy-1, and VAMP-2) were increased before markers of neurodegeneration are observed 39 .…”
Section: Discussioncontrasting
confidence: 76%
“…VGF has also been proposed as a biomarker of AD and its progression (42). Although CSF levels of VGF, a neuronal and neurosecretory protein, might be anticipated to decrease coincident with neuronal loss as AD progresses, it is important to note that in two biomarker studies, the CSF levels of a number of related neurosecretory and synaptic proteins, including chromogranin A, secretogranin II, 7B2, proSAAS, clusterin, neurexins 1, 2 and 3, and neuropentraxin 1 were either increased or unchanged in patients with AD compared to controls, while VGF levels consistently were reduced in AD patient CSF (41,44). Our systematic analysis of changes in gene expression and proteomic profiles in disease-free and AD brains identified VGF as not only strongly associated with AD, but as a key driver gene of our AD-associated network, a finding that is further supported by our direct perturbation of VGF in the 5xFAD mouse model.…”
Section: Discussionmentioning
confidence: 99%